IMPLEMENTATION OF THE AGILE METHODOLOGY IN A DIET AND BULKING MOBILE APPLICATION USING THE FLUTTER FRAMEWORK - Rahmat Syahrur Ramadhan; Nuril Lutvi Azizah; Ika Ratna Indra Astutik; Sumarno Sumarno (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to develop and evaluate the FitLaksana mobile application as a digital solution for improving dietary management and physical activity to address rising health issues such as obesity and metabolic disorders. Method: The application was developed using the Flutter framework and Firebase database, following the Agile methodology through stages of system analysis, user interface design, feature implementation, and Black Box testing. User evaluations were conducted using a Likert scale to assess satisfaction levels regarding functionality, usability, and reliability. Results: All features of the FitLaksana application operated effectively, with users reporting high satisfaction levels—50% rated the app “Agree” (score 4) and 65.38% rated “Strongly Agree” (score 5). The application was praised for its user-friendly interface, stability, and usefulness in supporting healthy lifestyle management. Novelty: This study introduces a comprehensive, user-centered mobile health application that integrates nutritional guidance and exercise planning, demonstrating the effective application of Agile-based development in creating practical digital health tools for self-managed wellness.